CLINICAL SPECTRUM OF SCRUB TYPHUS IN A TERTIARY CARE HOSPITAL AT EASTERN INDIA - Dhar, Srikant Kumar; Kabi, Sobhitendu; Das, Chandan; Samant, Swati; Tripathy, Debasmita; Kumar, Amit; Sahu, Mahesh Chandra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Our hospital, tertiary care hospital in the capital of the state of Odisha, had been witnessing pyrexia of unknown origin, associated with breathlessness, renal, and liver impairment, which did not respond to high antibiotics but to doxycycline; therefore, the present study was undertaken to identify whether scrub typhus is the etiological agent, and thereafter, their characteristic features were further evaluated as an effort in supporting its diagnoses and treating patients accordingly. Methods: A total of 65 adult patients (age >15 years) admitted with pyrexia between April 2015 and October 2017 were evaluated. Immunoglobulin M (IgM) scrub typhus test was done in all these patients. IgM scrub typhus test positive samples were included in the study and various clinical parameters analyzed. Results: Of the 65 patients included in the study, all were found to be positive for IgM antibodies against Orientia tsutsugamushi. The cases were seen mainly in the months between September and November. The common symptoms found were fever, myalgia, breathlessness, rash, and abdominal pain and rarely altered sensorium. The diagnostic features like eschar were found in 23% patients. Nearly, two-thirds of patients had fever more than 7 days and myalgia (76.92%), headache (58.46%). The most common complications were renal failure (20%) followed by pneumonia (10.76%). Laboratory findings of high C-reacting protein (89.23%) and leukocytosis are found in 35.38%. Conclusion: Our results showed that scrub typhus should be considered in the differential diagnosis of pyrexia of unknown origin associated with breathlessness, myalgia, rash, gastrointestinal symptoms, hepatorenal syndrome, or acute respiratory distress syndrome. Empirical treatment with doxycycline may be given in the cases with strong suspicion of scrub typhus.